Evaluation of Electrocoagulation for the Removal of Heavy Metals in Acid Mine Drainage (AMD): A Sustainable Alternative - Chávez Zamora, Diana Analy; Diaz Ruiz, Julian Ricardo; Oblitas Cruz, Jimy Frank (LACCEI, 2025)
This study evaluates the use of electrocoagulation with iron and aluminum electrodes to treat Acid Mine Drainage (AMD), focusing on removing heavy metals. The aim was to evaluate the effectiveness of electrocoagulation in removing heavy metals from AMD. The method included taking samples from the AMD, placing them in an electrocoagulation cell, and treating them for 10, 20, and 30 minutes with each type of electrode (iron and aluminum). This research allowed us to evaluate the removal capacity of the iron and aluminum electrodes in the electrocoagulation process, finding that aluminum electrodes have a greater capacity to remove heavy metals such as Mn, Fe, Cr, Cd, Cu, Co, Ni, Pb, and Zn, with removal rates ranging from 83% to 99.5% after 30 minutes. At the end of the process, water of category 3 is obtained, meaning it can be used for irrigation of plants and animal drinking water, according to DS N° 004-2017, which approves the Environmental Quality Standards (ECA) for Water in Peru.